2001
DOI: 10.1592/phco.21.18.302s.33905
|View full text |Cite
|
Sign up to set email alerts
|

What Do We Really Know About Antibiotic Pharmacodynamics?

Abstract: Antibiotic pharmacodynamics is an evolving science that focuses on the relationship between drug concentration and pharmacologic effect, which is an antibiotic-induced bacterial death that also can manifest as an adverse drug reaction. The pharmacologic action of antibiotics usually can be described as concentration dependent or independent, although such classifications are highly reliant on the specific antibiotic and bacterial pathogen being studied. Quantitative pharmacodynamic parameters, such as ratio of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
67
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 82 publications
0
67
0
3
Order By: Relevance
“…3 Besides quantitative pharmacodynamic parameters, such as AUC 0À24 :MIC, Cmax:MIC and T4MIC, which have been proposed as likely predictors of clinical and microbiological success, PAE provides potential influence on antimicrobial dosing regimens in clinical practice, where agents inducing a long PAE may be administered with longer dosing intervals than currently employed, without loss of efficacy. 9 Our experiments showed that durations of the PAE of amikacin were significantly increased in a concentration-dependent manner. When the concentration was increased to 20Â MIC, the increase in duration of PAEs were almost 2.5 times longer than when the agent was applied at concentrations equal to 1Â MIC (Po0.001; Figure 1).…”
Section: Discussionmentioning
confidence: 57%
“…3 Besides quantitative pharmacodynamic parameters, such as AUC 0À24 :MIC, Cmax:MIC and T4MIC, which have been proposed as likely predictors of clinical and microbiological success, PAE provides potential influence on antimicrobial dosing regimens in clinical practice, where agents inducing a long PAE may be administered with longer dosing intervals than currently employed, without loss of efficacy. 9 Our experiments showed that durations of the PAE of amikacin were significantly increased in a concentration-dependent manner. When the concentration was increased to 20Â MIC, the increase in duration of PAEs were almost 2.5 times longer than when the agent was applied at concentrations equal to 1Â MIC (Po0.001; Figure 1).…”
Section: Discussionmentioning
confidence: 57%
“…W przypadku antybiotyków wykorzystanie mierzalnej wrażliwo-ści czynnika etiologicznego in vitro (MIC) oraz podstawowych parametrów farmakokinetycznych pozwala określić efekt farmakodynamiczny [2,3]. Podstawowe wskaźniki PK/PD, dobrze korelujące ze skutecznością prowadzonej antybiotykoterapii, obejmują [4][5][6][7]:…”
Section: Wstępunclassified
“…W przypadku antybiotyków wykorzystanie mierzalnej wrażliwo-ści czynnika etiologicznego in vitro (MIC) oraz podstawowych parametrów farmakokinetycznych pozwala określić efekt farmakodynamiczny [2,3]. Podstawowe wskaźniki PK/PD, dobrze korelujące ze skutecznością prowadzonej antybiotykoterapii, obejmują [4][5][6][7]:• C max /MIC -stosunek szczytowego stężenia leku uzyskanego po pojedynczej dawce (C max ) do minimalnego stężenia hamującego MIC; • AUC 24 /MIC -stosunek pola pod krzywą zależności zmian stężenia leku we krwi od czasu w ciągu 24 godz. (AUC 24 ) do MIC; • T > MIC (%) -czas, w którym stężenie leku we krwi pozostaje powyżej MIC.…”
unclassified
“…For Ampicillin, its antibacterial activity depends on its bioavailability and on length of time it is able to maintain high concentration in blood of treated animals [6]. Differences in therapeutic actions of drugs made from same medicinal active ingredients but manufactured by different companies are reported to be due to interactions of components used in formulating the drugs and on stabilizing agents used [7].…”
Section: Introductionmentioning
confidence: 99%